RuvBL1 ATPase activity is essential for mitochondrial integrity and function in HCC cells. (March 2023) - Simeone, I.; Guida, A.; Polvani, S.; Ceni, E.; Bani, D.; Nardini, P.; Guasti, D.; Parri, M.; Santi, A.; Galli, A.; Mello, T.
Abstract : RuvBL1 is a AAA+ ATPase involved in multiple cellular activities, such as cell proliferation, chromatin remodeling, DNA repair, transcription, translation and mTOR pathway activity. High RuvBL1 expression in HCC correlates with worse prognosis. We previously demonstrated that RuvBL1 is a key regulator of liver metabolism and glucose homeostasis, suggesting that this ATPase may also participate in the metabolic rewiring of HCC cells. We therefore aimed at dissecting RuvBL1 role in HCC cell metabolism. Metabolomics performed by GC/MS in RuvBL1-silenced Huh7 cells highlighted altered intermediates of glucose, TCA and aminoacid metabolism. Pathway enrichment analysis of modulated metabolites showed a significant association with processes related to cancer metabolic reprogramming and centered in mitochondria. RuvBL1 targeting by RNAi or by the selective inhibitor CB-6644 significantly impaired OXPHOS and ATP production in a dose- and time-dependent manner in AML-12, Hepa1-6, Huh7, Hep3B and HepG2 cell lines. Mitochondrial morphology assessed by Mitotracker and TEM was severely affected by RuvBL1 inhibition, that caused a reduction in matrix electrondensity, disruption of the cristae, swelling and fragmentation. Using superresolution STED microscopy and immunoglold/TEM, we detected RuvBL1 within mitochondria. Thus, we performed MS analysis of RuvBL1 co-immunoprecipitated complexes from purified mitochondria. Gene ontology analysis of mitochondrial RuvBL1-interactome revealed that this ATPase impact on TCA, aminoacid, purines, and lipid metabolism, mito-ribosome assembly, mitochondrial transmembrane transport, and membrane organization. Intriguingly, several members of the MIB complex (SAMM50, Mic19, Mic60), which plays a crucial role in shaping mitochondrial cristae, were identified in the RuvBL1-interactome. In the TCGA-LIHC dataset, RuvBL1 expression positively correlates with 9 out of 14 principal members of the MIB complex and genes differentially expressed between HCC with high- vs low-RuvBL1 were significantly enriched in mitochondria-related GO terms. Our data uncover a novel localization and function of RuvBL1 in mitochondria, and suggest that RuvBL1 overexpression support mitochondria-related processes in HCC.